The molecular functions of auxin signaling in tomato (Solanum lycopersicum L.) - Silva, Willian Batista (2018)
The auxin is a phytohormone with intense participation in the growth and development process, as well as in crucial physiological processes to the plant establishment. Although its role in development control is already well established and has been extensively investigated, in our understanding, little or nothing is currently known about the impacts on the manipulation of the signaling levels of this hormone in the metabolic impact, as well as the link between auxin and photosynthetic and respiratory process both in leaves and fruit. In this vain, considering the metabolic importance in plant and the wide regulatory network of this system, in this thesis initially I present a review offering an important comparative complement of post-genomic strategies, such as the profile of the metabolites, providing information on the regulation of the metabolic network and thus allowing a more complete description of the cellular function of the plant. A comparative analysis was made by raising a question, if stable isotope mass spectrometry could replace radiolabelled approaches in metabolic studies? In addition, to better understand the functions of the modulation of auxin perception levels and how it conducts metabolic adjustments in different plant tissues, two experimental approaches were adopted for: (i) Characterize tomato plants with alterations in auxin signaling balance and their modulations in primary metabolism in tomato leaves and (ii) to analyze the role of auxin signaling in the ripening of tomato fruits. Briefly, the results indicate that auxin acts as an integrator of metabolism and adjustment and suggests that altered perceptions of this hormone affect the chloroplastic and mitochondrial metabolism in lighted leaves, suggesting a great participation of this phytohormone in the final productivity determination. Moreover, at the fruit level, auxin seems to control metabolic alterations very little, but controlling important steps in fruit maturation, controlling the metabolism of starch and sugars, providing new perspectives of integration between auxin and respiratory paths.